A tunable triboelectric wideband energy harvester. (July 2019) - Nelson, Daniel; Ibrahim, Alwathiqbellah; Towfighian, Shahrzad
The ability to efficiently convert mechanical energy into electrical energy has become an important topic of discussion and research in the last decade. Triboelectric generators have recently been popular for vibration energy harvesting, but despite plenty of research on its material aspect, research on combining mechanical characteristics and voltage generation output has been sparse. Many energy harvesters suffer from low operating bandwidths and are usually restricted to operating at a specific frequency. We propose a tunable triboelectric energy harvester that has a large response over a wide frequency bandwidth at low frequencies. The tunability is implemented by axially preloading a beam that reduces the system stiffness. This stiffness reduction strengthens the collisions that naturally occur in the triboelectric generators, resulting in larger voltage outputs. As the system stiffness decreases, the impacts occur over a broader frequency range, widening the frequency bandwidth. To describe the dynamic and voltage responses, a continuous electromechanical model is derived. The presented mathematical model sheds light on the coupled characteristics of mechanical vibration and triboelectric voltage generation, and can be used as a design tool for high-efficiency energy harvesters to operate wireless sensor networks.